2022
DOI: 10.1038/s41467-022-34620-y
|View full text |Cite|
|
Sign up to set email alerts
|

The SOD1-mediated ALS phenotype shows a decoupling between age of symptom onset and disease duration

Abstract: Superoxide dismutase (SOD1) gene variants may cause amyotrophic lateral sclerosis, some of which are associated with a distinct phenotype. Most studies assess limited variants or sample sizes. In this international, retrospective observational study, we compare phenotypic and demographic characteristics between people with SOD1-ALS and people with ALS and no recorded SOD1 variant. We investigate which variants are associated with age at symptom onset and time from onset to death or censoring using Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…In order to investigate whether WTL and MBR variants associate with different clinical outcomes, we collected clinical data of patients carrying the variants investigated in this study. We were able to retrieve clinical data of 489 ALS patients with A4V, G37R, L38V, G93R, I113T, H46R, H80R, G85R and D125H (see details of individual variants in Table 4) [34]. Cox proportional hazard analysis (Figure 10) showed that patients with MBR variants presented a longer survival time (approximately 6 years median difference, p < 0.001) than patients with WTL variants, while no difference (p = 0.19) was observed for the age of onset (details in Table 4).…”
Section: Phenotype Analysis Of Wtl and Mbr Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate whether WTL and MBR variants associate with different clinical outcomes, we collected clinical data of patients carrying the variants investigated in this study. We were able to retrieve clinical data of 489 ALS patients with A4V, G37R, L38V, G93R, I113T, H46R, H80R, G85R and D125H (see details of individual variants in Table 4) [34]. Cox proportional hazard analysis (Figure 10) showed that patients with MBR variants presented a longer survival time (approximately 6 years median difference, p < 0.001) than patients with WTL variants, while no difference (p = 0.19) was observed for the age of onset (details in Table 4).…”
Section: Phenotype Analysis Of Wtl and Mbr Variantsmentioning
confidence: 99%
“…Our results suggested that the structural and dynamic behaviour differences between WTL and MBR variants could be linked to the ALS clinical phenotype. To explore this hypothesis, we collected a large clinical dataset of SOD1 ALS patients [34] and performed survival and age of onset analyses in the patients carrying WTL and MBR variants.…”
Section: Introductionmentioning
confidence: 99%
“…This design would not reflect motor neuron-specific ALS pathogenesis. Other studies adopted a case-control framework 8,9,11 , which could lead to reduced power given the potential decoupling between mechanisms underlying risk and clinical presentation [13][14][15] . Furthermore, previous work has not been validated in independent datasets or in different populations and did not investigate whether molecular subtypes identified in post-mortem brains are reflected in other tissues available pre-mortem.…”
Section: Introductionmentioning
confidence: 99%
“…As well as affecting ALS risk, some of these variants have distinct effects on clinical features such as age of onset of motor symptoms and disease duration. For example, p.A5V and p.H44R have a marked effect on disease duration while p.G38R is associated with an early onset 10,12-14 . Being able to characterise how genetic variants affect the clinical phenotype is essential for optimal development and design of healthcare, treatments, and trial stratification.…”
Section: Introductionmentioning
confidence: 99%